Corpus Christi Simplicioribus: alegorías y representación de la autoridad en Valencia - Martin, Vincent T. (Revista de dialectología y tradiciones populares, 1992)
In this paper I study the Valencian Corpus Christi play «El misteri del Rey Herodes» in its social and textual setting. I analyze the notion of representation and allegory, and how these concepts lead to a textual unfolding ad infinitum, thus erasing all boundaries between actor and spectator. I attempt to disprove the common misconception that the misteris are a minor literary genre, and in fact serve as a sort of social framework for the urban center, as does law. I test the validity of Walter Benjamin's theories of divine and mythical violence through King Herod's confrontation with Christ. And I examine as well the process of creating the festa: active participation. This is the key to the festa, since the play is only part of the spectacle.